Evaluation of lap-splices in NSM FRP rods for retrofitting RC members. (April 2021) - M. A. Kadhim, Majid; Jawdhari, Akram; Peiris, Abheetha
Abstract: Externally Bonded FRP (EB-FRP) and Near Surface Mounted (NSM) FRP are the two common forms of utilizing FRP material for flexural strengthening of Reinforced Concrete (RC) members. While the design and construction of EB-FRP is well established, there are several gaps in the current knowledge base regarding strengthening using NSM FRP. One area where research in NSM FRP is limited is on splicing of the NSM FRP rods/strips. Splicing becomes extremely advantageous when strengthening bridge beams spanning over multi-lane traffic lanes, or when strengthening long spans where it may be more economical to carry out the retrofit in stages. The present study evaluates the feasibility of lap-splicing NSM FRP rods using finite element analysis (FEA). Several experimentally evaluated NSM FRP strengthened RC beams available in literature were modeled using finite elements. The developed FE models are validated based on a comparative study of the experimental and FEA predicted test results. The calibrated FE models are then utilized to evaluate different methods of splicing configurations for NSM FRP rods. The development length for each configuration is evaluated and the best methods identified. A parametric study is then carried out varying geometric and material properties to evaluate their effect on the development length and beam behavior. The required splice length is found to be a function of FRP rod diameter and FRP modulus, but invariant of concrete compressive strength. A design splice length of 110 times the FRP rod diameter is recommended for concrete strengths between 15 and 45 MPa and FRP rod diameters between 6 and 10 mm.